Experimental and numerical study of mechanical properties of multi-phase medium-Mn TWIP-TRIP steel: Influences of strain rate and phase constituents. (15th September 2019) - Benzing, J.T.; Liu, Y.; Zhang, X.; Luecke, W.E.; Ponge, D.; Dutta, A.; Oskay, C.; Raabe, D.; Wittig, J.E.
Abstract: In the current work we investigate the room temperature tensile properties of a medium-Mn twinning- and transformation-induced plasticity (TWIP-TRIP) steel from quasi-static to low-dynamic strain rates ( ε ˙ = 10 −4 s −1 to ε ˙ = 10 2 s −1 ). The multi-phase microstructure consists of coarse-grained recovered α ' -martensite (inherited from the cold-rolled microstructure), multiple morphologies of ultrafine-grained (UFG) austenite (equiaxed, rod-like and plate-like), and equiaxed UFG ferrite. The multi-phase material exhibits a positive strain-rate sensitivity for yield and ultimate tensile strengths. Thermal imaging and digital image correlation allow for in situ measurements of temperature and local strain in the gauge length during tensile testing, but Lüders bands and Portevin Le Chatelier bands are not observed. A finite-element model uses empirical evidence from electron backscatter diffraction (EBSD) and transmission electron microscopy (TEM), plus constitutive equations to dissect the microstructural influences of grain size, dislocation density and TWIP-TRIP driving forces on tensile properties. Calibration of tensile properties not only captures the strain rate sensitivity of the multi-phase TWIP-TRIP steel, but also provides opportunity for a complete parametric analysis by changing one variable at a time (phase fraction, grain size, strain-induced twin fraction and strain-induced ε -martensite fraction). An equivalent set of high-rate mechanical properties can be matched by changing either the austenite phase fraction or the ratio of twinning vs. transformation to ε -martensite. This experimental-computational framework enables the prediction of mechanical properties in multi-phase steels beyond the experimental regime by tuning variables that are relevant to the alloy design process. Graphical abstract: Image 1